Rapidly Changing Cities: Working with Socio-Ecological Systems to Facilitate Transformation - Landman, Karina (2021)
Cities across the world are changing rapidly. Driven by population growth, migration, economic decline in rural areas, political instabilities, and even more recently, the Covid-19 pandemic, urban systems and spaces are changing to accommodate moving people and new functions. In many cases, these trends contribute to increased levels of inequality, poverty, food insecurity, and unemployment, while the warnings about the impact of climate change continue to raise concerns. Though some have called this a new urban revolution, others have referred to, in a more apocalyptic turn, the end of cities. In response, many writers are encouraging smarter cities, whereas others are promoting a post-urban context and a return to small communities. High levels of uncertainty are characteristic, along with increased intensities of complexity, rapid fluctuation and unbounded experimentation. This raises many questions about the nature and implication of change in different cities situated in vastly contrasting contexts. This thematic issue of Urban Planning focuses on five narratives from cities across the world to illustrate various drivers of change and their implications for urban design and planning. The editorial introduces these narratives, as well as commentaries from leading academics/practitioners and highlights several divergent experiences and common threats. It argues that to deal with the rapid and often large-scale changes, planners need to view human settlements as socio-ecological systems and plan for change and uncertainty to facilitate the co-evolution of humans and nature.